Masculine depression and its problem behaviors: use alcohol and drugs, work hard, and avoid psychiatry!$doriginal paper - Zimmermann, Claudia von; Hübner, Magdalena; Mühle, Christiane; Müller, Christian P.; Weinland, Christian; Kornhuber, Johannes; Lenz, Bernd (European archives of psychiatry and clinical neuroscience, 2023)
The gender role influences vulnerability to mental illness. Substance use, even critical in scale, is perceived as masculine, just like hard (over-)work, while not seeking help. With the ongoing separation between gender and sex, masculine norms become more relevant also to females’ mental health. The male depression concept highlights the role of male symptoms in affective disorders. However, the empirical evidence is still limited. Here, we use the denomination ‘masculine depression’ to open the category for female patients and tested substance use patterns, health services’ utilization, and working hours as predictors in a case-control study of 163 depressed in-patients (44% women; masculine vs. non-masculine depression according to a median split of the Male Depression Rating Scale-22) and 176 controls (51% women). We assessed higher depression severity in patients with masculine (vs. non-masculine) depression. Masculine depression (vs. non-masculine depression and vs. no depression) was predicted by more frequent and critical use of alcohol (including binge drinking), tobacco, and illicit drugs, and by longer working times. Moreover, fewer health services contacts due to mental complaints during the previous year were associated with masculine (vs. non-masculine) depression. Alarmingly, even critical substance misuse was not significantly associated with more frequent health services contacts; however, the higher the depression severity, the more contacts the patients reported. Here, we provide evidence that patients with masculine depression are highly burdened and undertreated, which applies equally to female and male patients. This study identified promising targets to establish specialized care offers.